Characterization of the endophytic bacterial community of Bituminaria bituminosa plant grown in vitro and its interaction with the plant extract - Chiellini, Carolina; De Leo, Marinella; Longo, Vincenzo; Pieracci, Ylenia; Pistelli, Laura (Frontiers in Plant Science, 2023)
uminaria bituminosa is a medicinal plant recognized for its phytochemicals, such as furanocoumarins, pterocarpans, and flavonoids. Since the secondary metabolism is influenced by the plant-endophyte interactions, the endophytic bacterial community of B. bituminosa was explored and the possible interactions with the plant were described. Different bacterial strains were isolated from different organs of in vitro plants as shoots, roots, and seeds. The bacterial strains were identified and phenotypically characterized for different traits; strains were also exposed to different concentrations of B. bituminosa plant extract showing different susceptibility, probably determined by different secondary metabolites produced by the plant in the different organs (i.e. aerial parts and roots). Bacterial strains showed different phenotypic characteristics; the 6 detected haplotypes were dominated by a single species related to Stenotrophomonas rhizophila. Endophytes isolated from the aerial parts produced a higher indole-3-acetic acid (IAA) amount than those of the roots, while all strains were unable to produce biosurfactants and antagonistic activity toward the other strains. The research opens new perspectives for future analysis addressed to test the susceptibility of the endophytic bacterial community of B. bituminosa toward the pure compounds extracted from the plants, and to investigate the role of these compounds on the distribution of endophytes within the different plant tissues.